Complications of Two Port Laparoscopic Cholecystectomy-Studyof 50 Cases - Mahmud, Nasir Uddin; Uddin, Ghyas; Haque, Md Anwarul; Haque, ANM Mozammel; Kibria, AKM Golam (TAJ: Journal of Teachers Association, 2019)
Background: For the management of Gallstone disease, laparoscopic cholecystectomy has been the the gold standard and is preferred over open cholecystectomy. As patients’ demand has increased for improved postoperative quality of life and cosmesis, surgeons have continued to decrease the number of ports for laparoscopic cholecystectomy. To meet these expectations we adopted two-port techniques at Comilla, Bangladesh. For the last three years we have selected 50 patients where two-port laparoscopic cholecystectomy was trialled. The procedure were successfully performed in 47(94%) & conversion were required in 3(6%) with some accepted complications like epigastric port infection & herniation, post cholecystectomy syndrome, reactionary haemorrhage, bile leakage & biloma, significant epigastric port pain postoperatively & stricture of CBD. The present two port technique not only overcoming specimen extraction difficulties but also contributes to good cosmesis. Objectives: To see the outcome of two port laparoscopic cholecystectomy. Methods: Consecutive 50 patients were admitted in surgery ward of Central medical college, Comilla with gallstone disease over a 3 years period. Diagnosis is confirmed by ultrasound with the assessment of operative feasibility. Data collection sheet was maintained by Microsoft Excel. Data were analyzed manually. Results: In this study 50 patients were included. Among them 34 (68%) were females and 16 (32%) were males (ratio = 2.1:1). Mean age was 35.7 years (range 20–55years).All patient were undergone two port laparoscopic cholecystectomy & successfully accomplished in 47 (94%),conversion were required in 3 (6%) patients. Most common (62%) sonological findings were cholelithiasis with normal size & shape of gall bladder. Mean operative time was 50 minutes. Among the per operative difficulties bleeding were 14%, perforation of gall bladder 10%, spillage of gallstones 6%, epigastric forceps manipulation difficulties 4%,conversion to open cholecystectomy 6%. Most of the patients(80%) admitted in hospital for 2-3 days. 4 (8%) patient had epigastric port infection & 1 (2%) patient developed this site herniation, 3 (6%) patient had post cholecystectomy syndrome,1 (2%) patient had reactionary haemorrhage, 1 (2%) bile leakage & biloma,4(8%) patient had significant epigastric port pain postoperatively, 1 (2%) patient developed delayed stricture of CBD. In all other patients wound healed nicely with minimal scarring, with very less postoperative pain, with no problem so far in 3 years follow up. Most patients (90%) returned to work within 2 weeks. Conclusion: Two-port laparoscopic cholecystectomy is a safe procedure & cosmetically rewarding. TAJ 2018; 31(1): 29-37